A hydrogen fuel cell cathode catalyst and preparation method thereof
Through thermal -solving legal preparation and modified graphene carrier catalyst, the problem of catalytic activity and stability in hydrogen fuel cells in hydrogen fuel cells in hydrogen fuel cells, realized efficient oxidation reaction catalysis, reduced the amount of platinum, and significantly increased the improvement of the amount of platinum, and significantly increased the improvement Electric catalytic activity and stability.
Patent Information
- Application Number
- CN202410883611.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-03
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-07-03
AI Technical Summary
The platinum-based catalysts used in existing hydrogen fuel cells are insufficient in catalytic activity and stability due to the noble metal properties, susceptibility to toxication and agglomeration, and it is difficult to meet the higher catalytic efficiency requirements of redox reactions.
The catalyst catalyst of the hydrogenation fuel cells is used, and the modified oxide graphene is used as a carrier to reduce the reunion of platinum, increase the dispersal of platinum particles, and enhance the catalytic activity by doping B, N, and S elements.
The catalytic efficiency of the reaction catalysis is achieved with a small amount of platinum, which improves catalytic activity and stability, reduces the amount of platinum, and significantly enhances the electrocatalytic activity and electrochemical stability of the catalyst.
Smart Images

Figure BDA0004925323100000071 
Figure BDA0004925323100000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fuel cells, and in particular, relates to a cathode catalyst for a hydrogen fuel cell and a preparation method thereof. Background Art
[0002] With the development of society, issues such as global energy consumption and climate change have attracted widespread attention. In addition, as fossil energy reserves are decreasing, it is urgent to find alternative new energy sources. At present, new energy sources under development include solar energy, wind energy and fuel cells. Among them, hydrogen fuel cells are a power generation device that directly converts the electrochemical reaction energy of hydrogen and oxygen into electrical energy. It is not only cheaper than traditional fossil fuels, but also has the advantages of cleanliness and high efficiency. It can also be combined with nuclear energy, biomass, solar energy, wind energy and other power generation technologies to diversify, renew and sustain energy use. It is considered to be the preferred clean energy power generation technology in the 21st century.
[0003] The cathode redox kinetics of hydrogen fuel cells are slow, so a catalyst needs to be added. The most commonly used cathode catalysts in hydrogen fuel cells are mainly platinum-based catalysts, because platinum-based catalysts have high redox catalytic activity, but platinum is a precious metal, expensive, and scarce in resources; it is easily poisoned by organic fuels, which reduces the catalyst life, and platinum catalysts are easy to aggregate, reducing the catalytic effect.
[0004] Researchers have developed many new non-platinum-based cathode catalysts in recent years. Although some progress has been made, the most effective catalytic material is still platinum catalyst. Therefore, it is urgent to invent a high-quality low-platinum catalyst to meet the higher demands in the field of fuel cell technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a hydrogen fuel cell cathode catalyst and a preparation method thereof.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A method for preparing a cathode catalyst for a hydrogen fuel cell comprises the following steps:
[0008] The modified graphene oxide is added to a chloroplatinic acid aqueous solution (mass concentration 5 g / L), and ultrasonicated at 30-50°C for 1-2 hours to uniformly disperse the modified graphene oxide, and then freeze-dried to obtain a dry powder; the dry powder is placed in a horizontal tubular furnace, an inert gas is introduced as a protective gas, and the temperature is increased to 450-500°C at a heating rate of 5°C / min in the tubular furnace, and after keeping the temperature for 1 hour, the powder is cooled to room temperature and taken out to obtain a hydrogen fuel cell cathode catalyst.
[0009] Furthermore, the ratio of the modified graphene oxide to the aqueous solution of chloroplatinic acid is 5-10 g:100-200 mL.
[0010] Furthermore, the inert gas is one of nitrogen, argon and a hydrogen-argon mixed gas.
[0011] Furthermore, during the heat preservation process, air extraction and ventilation are performed every 20 minutes.
[0012] The thermal decomposition method is used to reduce chloroplatinic acid to produce platinum, which is then deposited on graphene oxide. Compared with the liquid phase method for preparing graphene-based catalysts, this method reduces the steps of washing and filtering, and the experimental conditions are easier to control. Using graphene oxide as a carrier can effectively improve the dispersion of platinum particles and slow down their agglomeration, thereby improving the catalytic activity and stability of platinum, and achieving higher catalytic efficiency of redox reactions with a small amount of platinum.
[0013] Furthermore, the modified graphene oxide is prepared by the following steps:
[0014] S1. Add graphite powder, potassium nitrate and potassium permanganate to concentrated sulfuric acid solution (mass fraction 98%) in sequence, stir for 10 minutes, then heat to 45°C, continue stirring for 30 minutes, gradually add distilled water, and dropwise add hydrogen peroxide aqueous solution (mass fraction 25%), observe that the solution turns bright yellow, stop dropping, filter, wash sulfate ions with hydrochloric acid solution (mass fraction 12%) and distilled water, and vacuum dry to obtain graphene oxide; the ratio of concentrated sulfuric acid solution, graphite powder, potassium nitrate, potassium permanganate, and distilled water is 25mL:2g:1g:5g:50mL;
[0015] Graphene oxide was prepared using the Hummers modified method;
[0016] S2. Add graphene oxide to sodium hydroxide solution (mass fraction 18%), start magnetic stirring at room temperature, set the reaction temperature to 110° C., react for 12 h, and after the reaction is completed, wash with water until neutral, and vacuum dry to obtain hydrophilic modified graphene oxide; the ratio of graphene oxide to sodium hydroxide solution is 1 g:50 mL;
[0017] The graphene oxide is hydrophilically modified to convert the hydrophobic epoxy groups on its surface into hydrophilic -OH and -ONa groups to obtain hydrophilic modified graphene oxide;
[0018] S3, in a three-necked flask equipped with a stirring device, the hydrophilic modified graphene oxide and N, N-dimethylformamide were mixed, mechanically stirred for 30 min, ultrasonically treated for 45 min, dithioaminopropionic acid and dicyclohexylcarbodiimide (DCC, dehydrating agent) were added and mixed and stirred evenly, and the mixture was kept warm at 55 ° C for 8 h, stirring was continued during the reaction, and the reaction was completed, filtered, washed, and freeze-dried to obtain doped graphene oxide; the ratio of the amount of hydrophilic modified graphene oxide, N, N-dimethylformamide, dithioaminopropionic acid, and dicyclohexylcarbodiimide was 1g:50mL:7g:12g;
[0019] The hydrophilic modified graphene oxide reacts with dithioaminopropionic acid to introduce S and N elements;
[0020] S4. Mix the doped graphene oxide with deionized water in a flask, perform ultrasonic treatment for 2 hours to evenly disperse the doped graphene oxide, place in a 75°C water bath, slowly add sodium borohydride under vigorous stirring, perform reduction reaction for 8 hours, vacuum dry, grind, and obtain modified graphene oxide; the ratio of doped graphene oxide, deionized water, and sodium borohydride is 1 g:100 mL:2 g;
[0021] The obtained modified graphene oxide has a much higher specific surface area than carbon nanotubes and graphite. It is a porous structure with good electrical conductivity and high resistance to electrochemical corrosion. It not only serves as a carrier of platinum catalyst, but also has a catalytic effect itself, reducing the amount of platinum used and improving the electrocatalytic property and stability of platinum catalyst. By hydrophilic modification of graphene oxide, compared with ordinary graphene oxide, the hydrophilicity is enhanced and it is not easy to agglomerate. The specific surface area of modified graphene oxide is also enhanced, the catalytic performance is further improved, and more reactive groups are provided for subsequent modification. The graphene oxide is doped with three elements, B, N, and S, among which B and N are doped into the graphene oxide sp 2 The lone electron pairs in the hybridized carbon skeleton can form a delocalized conjugated system with the large π bonds of graphene oxide, which changes the charge distribution and spin density of C atoms in graphene oxide, thereby generating active sites on the surface of graphene oxide that are conducive to redox reactions and greatly improving its electrocatalytic activity; and S-doped graphene oxide can increase the porosity and specific surface area of graphene oxide, increase the loading amount of platinum catalysts, and improve electrocatalytic activity.
[0022] Beneficial effects of the present invention:
[0023] 1. The present invention uses a thermal decomposition method to prepare the catalyst, which reduces the steps of washing and filtering compared to the liquid phase method, and the experimental conditions are easy to control;
[0024] 2. Using graphene oxide as a platinum catalyst carrier can effectively improve the dispersion of platinum particles and slow down their agglomeration, thereby improving the catalytic activity and stability of platinum, and achieving higher redox reaction catalytic efficiency with a small amount of platinum;
[0025] 3. By modifying graphene oxide, compared with ordinary graphene, the agglomeration phenomenon is reduced, the dispersion is more uniform, the platinum loading capacity is high, the electrocatalytic activity of the catalyst is significantly enhanced, and the amount of platinum is reduced;
[0026] Therefore, the catalyst prepared by the present invention has strong electrocatalytic activity, high catalytic efficiency, reduced platinum usage, and strong electrochemical stability, and has important application value in the field of fuel cell technology. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] Preparation of modified graphene oxide:
[0030] S1. Add 2g of graphite powder, 1g of potassium nitrate and 5g of potassium permanganate to 25mL of concentrated sulfuric acid solution (mass fraction 98%) in sequence, stir for 10min, then heat to 45°C, continue stirring for 30min, gradually add 50mL of distilled water, and dropwise add aqueous hydrogen peroxide solution (mass fraction 25%), observe that the solution turns bright yellow, stop dropping, filter, wash sulfate ions with hydrochloric acid solution (mass fraction 12%) and distilled water, and vacuum dry to obtain graphene oxide;
[0031] S2, adding 1g of graphene oxide to 50mL of sodium hydroxide solution (mass fraction 18%), turning on magnetic stirring at room temperature, setting the reaction temperature to 110°C, reacting for 12h, and washing with water to neutrality, and vacuum drying to obtain hydrophilic modified graphene oxide;
[0032] S3, in a three-necked flask equipped with a stirring device, 1g of hydrophilic modified graphene oxide was mixed with 50mL of N,N-dimethylformamide, mechanically stirred for 30min, ultrasonically treated for 45min, 7g of dithioaminopropionic acid and 12g of dicyclohexylcarbodiimide were added, mixed and stirred evenly, and the mixture was kept warm at 55°C for 8h, with continuous stirring during the reaction. After the reaction was completed, the mixture was filtered, washed, and freeze-dried to obtain doped graphene oxide;
[0033] S4. Mix 1 g of doped graphene oxide with 100 mL of deionized water in a flask, and perform ultrasonic treatment for 2 h to evenly disperse the doped graphene oxide. Place the mixture in a 75°C water bath, and slowly add 2 g of sodium borohydride under vigorous stirring. After the reduction reaction for 8 h, vacuum dry the mixture, and grind it to obtain modified graphene oxide.
[0034] Example 2
[0035] Preparation of modified graphene oxide:
[0036] S1. Add 4 g of graphite powder, 2 g of potassium nitrate and 10 g of potassium permanganate to 50 mL of concentrated sulfuric acid solution (mass fraction 98%) in sequence, stir for 10 min, then heat to 45 ° C, continue stirring for 30 min, gradually add 100 mL of distilled water, and dropwise add aqueous hydrogen peroxide solution (mass fraction 25%), observe that the solution turns bright yellow, stop dropping, filter, wash sulfate ions with hydrochloric acid solution (mass fraction 12%) and distilled water, and vacuum dry to obtain graphene oxide;
[0037] S2, adding 2g of graphene oxide to 100mL of sodium hydroxide solution (mass fraction 18%), turning on magnetic stirring at room temperature, setting the reaction temperature to 110°C, reacting for 12h, and washing with water until neutral, and vacuum drying to obtain hydrophilic modified graphene oxide;
[0038] S3, in a three-necked flask equipped with a stirring device, 2g of hydrophilic modified graphene oxide was mixed with 100mL of N,N-dimethylformamide, mechanically stirred for 30min, ultrasonically treated for 45min, 14g of dithioaminopropionic acid and 24g of dicyclohexylcarbodiimide were added and mixed and stirred evenly, and the mixture was kept warm at 55°C for 8h, with continuous stirring during the reaction. After the reaction was completed, the mixture was filtered, washed, and freeze-dried to obtain doped graphene oxide;
[0039] S4. Mix 2 g of doped graphene oxide with 200 mL of deionized water in a flask, and perform ultrasonic treatment for 2 h to evenly disperse the doped graphene oxide. Place the mixture in a 75°C water bath, and slowly add 4 g of sodium borohydride under vigorous stirring. After the reduction reaction for 8 h, vacuum dry the mixture, grind the mixture, and obtain modified graphene oxide.
[0040] Example 3
[0041] 5 g of the modified graphene oxide obtained in Example 1 was added to 100 mL of chloroplatinic acid aqueous solution (mass concentration 5 g / L), and the modified graphene oxide was evenly dispersed after ultrasonic treatment at 30° C. for 1 h, and then freeze-dried to obtain a dry powder; the dry powder was placed in a horizontal tubular furnace, nitrogen was introduced as a protective gas, and the temperature was increased to 450° C. at a heating rate of 5° C. / min in the tubular furnace. During the insulation process, the gas was evacuated and ventilated every 20 min. After insulation for 1 h, the mixture was cooled to room temperature with the furnace and taken out to obtain a hydrogen fuel cell cathode catalyst.
[0042] Example 4
[0043] 7.5 g of the modified graphene oxide obtained in Example 1 was added to 150 mL of a chloroplatinic acid aqueous solution (mass concentration of 5 g / L), and the modified graphene oxide was evenly dispersed after ultrasonic treatment at 40° C. for 1.5 h. The powder was then freeze-dried to obtain a dry powder. The dry powder was placed in a horizontal tubular furnace, and a hydrogen-argon mixed gas was introduced as a protective gas. The temperature was increased to 475° C. at a heating rate of 5° C. / min in the tubular furnace. During the insulation process, the gas was evacuated and ventilated every 20 min. After insulation for 1 h, the powder was cooled to room temperature with the furnace and taken out to obtain a hydrogen fuel cell cathode catalyst.
[0044] Example 5
[0045] 10 g of the modified graphene oxide obtained in Example 1 was added to 200 mL of chloroplatinic acid aqueous solution (mass concentration 5 g / L), and the modified graphene oxide was evenly dispersed after ultrasonic treatment at 50° C. for 2 h, and then freeze-dried to obtain a dry powder; the dry powder was placed in a horizontal tubular furnace, argon was introduced as a protective gas, and the temperature was increased to 500° C. at a heating rate of 5° C. / min in the tubular furnace. During the insulation process, the gas was evacuated and ventilated every 20 min. After insulation for 1 h, the mixture was cooled to room temperature with the furnace and taken out to obtain a hydrogen fuel cell cathode catalyst.
[0046] Comparative Example 1
[0047] Ordinary graphene of the same mass was used, and the remaining steps were the same as those in Example 5.
[0048] Comparative Example 2
[0049] A commercially available fuel cell platinum-carbon catalyst (Pt 40%) produced by Suqian Yisheng Metal Materials Co., Ltd. was used.
[0050] The dispersion of Pt in the supported catalysts of Examples 3-5 and Comparative Examples 1-2 was measured by CO gas pulse method; and the specific surface area of the catalysts was tested;
[0051] The catalysts of Examples 3-5 and Comparative Examples 1-2 were coated on a glassy carbon electrode for catalytic testing, wherein a saturated calomel electrode was used as a reference electrode, a platinum wire electrode was used as a counter electrode, and a glassy carbon electrode coated with the catalyst sample was used as a working electrode;
[0052] The preparation method of the working electrode is as follows:
[0053] The catalyst was prepared into a mixed solution of deionized water and anhydrous ethanol (1:1) with a concentration of 5 mg / ml. After ultrasonication for 10 minutes, 8 μL (4 μL each time) was pipetted with a micropipette and dropped onto the polished rotating disk electrode. It was allowed to dry naturally in the air. Then, 8 μL of anhydrous ethanol solution with a mass fraction of 0.05% was dropped onto the electrode surface and allowed to dry naturally.
[0054] Cyclic voltammetry was used to measure the initial potential and half-wave potential after 3000 cycles;
[0055] The measured results are shown in the following table:
[0056]
[0057]
[0058] It can be seen from the above table that the catalyst prepared in the embodiment of the present invention has better dispersion and specific surface area than the comparative example, and has strong electrocatalytic activity and electrochemical stability, and has important application value in the field of fuel cell technology.
[0059] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0060] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a cathode catalyst for a hydrogen fuel cell, characterized in that: The following steps are involved: The modified graphene oxide is added to a chloroplatinic acid aqueous solution, and after ultrasonication at 30-50°C for 1-2 hours, freeze-dried to obtain a dry powder; the dry powder is placed in a horizontal tube furnace, an inert gas is introduced, and the temperature is increased to 450-500°C at a heating rate of 5°C / min in the tube furnace, and after keeping the temperature for 1 hour, the powder is cooled to room temperature with the furnace and taken out; Wherein, the modified graphene oxide is prepared by the following steps: S1. Add graphite powder, potassium nitrate and potassium permanganate to concentrated sulfuric acid solution in sequence, stir for 10 minutes, then heat to 45°C, continue stirring for 30 minutes, add distilled water, and dropwise add aqueous hydrogen peroxide solution. When the solution turns bright yellow, stop dropping, filter, wash with water, and vacuum dry to obtain graphene oxide; S2, adding graphene oxide to sodium hydroxide solution, stirring at room temperature, setting the reaction temperature to 110° C., reacting for 12 h, and washing with water until neutral, and vacuum drying to obtain hydrophilic modified graphene oxide; S3, mixing the hydrophilic modified graphene oxide with N,N-dimethylformamide, stirring for 30 minutes, ultrasonically treating for 45 minutes, adding dithioaminopropionic acid and dicyclohexylcarbodiimide, mixing and stirring evenly, reacting at 55° C. for 8 hours, stirring continuously during the reaction, filtering, washing, and freeze-drying to obtain doped graphene oxide; S4. Mix the doped graphene oxide with deionized water, ultrasonically treat for 2 hours, place in a 75°C water bath, add sodium borohydride under vigorous stirring, react for 8 hours, vacuum dry, and grind to obtain modified graphene oxide.
2. The method for preparing a cathode catalyst for a hydrogen fuel cell according to claim 1, characterized in that: In step S1, the ratio of the amount of concentrated sulfuric acid solution, graphite powder, potassium nitrate, potassium permanganate and distilled water is 25mL:2g:1g:5g:50mL.
3. The method for preparing a cathode catalyst for a hydrogen fuel cell according to claim 1, characterized in that: In step S2, the ratio of graphene oxide to sodium hydroxide solution is 1 g:50 mL.
4. The method for preparing a cathode catalyst for a hydrogen fuel cell according to claim 1, characterized in that: In step S3, the ratio of the amount of hydrophilic modified graphene oxide, N,N-dimethylformamide, dithioaminopropionic acid, and dicyclohexylcarbodiimide is 1 g:50 mL:7 g:12 g.
5. The method for preparing a cathode catalyst for a hydrogen fuel cell according to claim 1, characterized in that: In step S4, the ratio of the amount of doped graphene oxide, deionized water, and sodium borohydride is 1 g:100 mL:2 g.
6. The method for preparing a cathode catalyst for a hydrogen fuel cell according to claim 1, characterized in that: The ratio of the modified graphene oxide to the chloroplatinic acid aqueous solution is 5-10 g:100-200 mL.
7. The method for preparing a cathode catalyst for a hydrogen fuel cell according to claim 1, characterized in that: The inert gas is one of nitrogen, argon and hydrogen-argon mixed gas.
8. A cathode catalyst for a hydrogen fuel cell, characterized in that: Prepared according to the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Platinum-carbon catalyst as well as preparation method and application thereof
CN114430045A
Graphene-loaded platinum-based catalyst and preparation method thereof
CN114976053A